Analysis of Student Learning Difficulties in Online Learning Excretory System Material at Junior High School of SMP Negeri 2 Pinogaluman - Al-Hamid, Nurjihan Nissa; Ahmad, Jusna; Dama, Lilan; Nusantari, Elya; Solang, Margaretha; Lamondo, Djuna (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Online learning is a learning system that uses internet media in the learning process. Applications that are usually used in online learning are WhatsApp, Youtube, google meet, google Classroom, and other online media. This study aims to determine the difficulties experienced by students during the online learning process on excretory system material at SMP Negeri 2 Pinogaluman. The subjects of the study were classes VIIIA and VIIIB SMP Negeri 2 Pinogaluman for the 2021/2022 Academic Year with a total of 40 respondents. The form of research is Quantitative Description. Data collection techniques in this study were carried out by survey method, namely by distributing questionnaires using internal factors consisting of cognitive, affective, interest, motivation, and intelligence indicators and using external factors consisting of indicators of the family environment, community environment, and government environment to students. Based on the results of the study, it can be concluded that students experience learning difficulties during the online learning process of excretory system material. The percentage of internal factors and external factors that affect learning difficulties is 66% which indicates that student response is low so that students experience high learning difficulties. Students experience difficulties in cognitive aspects with an average low percentage of reasoning ability of 49%